What makes a real patient? - Snow, R (BMJ Publishing Group, 2016)
A few years ago I applied for a grant to study my own long term condition. I started out as Ms Snow, ashamed of saying the name of my disease, and ended up Dr Snow, the type 1 diabetic, knowing a lot more about research and academia than I ever thought I would. I realised that patients can see things in research that clinicians can’t because we think to look in new places, and we spot discrepancies that doctors take for granted. I became particularly interested in power relations, and then in the things that stop patients having a say in what gets researched in the first place.